The Abuse of Power in The Hunger Games, Divergent, and Matched - Ratih Kuswidyasari; Ali Mustofa; Widyastuti (International Journal of Pedagogical Language, Literature, and Cultural Studies (i-Plural), 2025)
Dystopian literature offers readers a portrayal of a bleak world where society functions under the rulers’ abuse. Emerging in the 20th century as a response to world events such as the First World War, dystopian literature emphasizes the supremacy of hostile social forces. Society is responsible for degrading its system and quality of living, as instigated by the government, technology, and commercialization. Those in power abuse their authority through various outlets to justify maintaining law and order. What is depicted in the dystopian literature somewhat represents the factual events happening globally, where governments worldwide abuse their power against their citizens. This research was conducted using a qualitative descriptive method because this method was used to analyse the abuse of power by the authority and other characters in three dystopian novels, The Hunger Games, Divergent, and Matched. The primary data is in the form of narratives and conversations between the characters, containing the abuse of power in those novels. Literary data collection was used to collect relevant data from the novels. Data analysis uses content and narrative analyses, including data compression and interpretation. Furthermore, the abuse of power is practiced by the government and other characters who hold positions of power. This article explores the practice of power abuse in three dystopian novels, exercised by both the former and the latter, to others in misguided attempts to sustain the status quo or any abhorrent values and beliefs.